2008
DOI: 10.1088/0953-2048/21/3/034008
|View full text |Cite
|
Sign up to set email alerts
|

Vortex pinning in chemical solution nanostructured YBCO films

Abstract: A methodology of general validity to study vortex pinning in YBa 2 Cu 3 O 7−δ (YBCO) is described. It is based on measuring the angular-dependent critical current density in a large range of temperatures and magnetic fields and it permits one to identify, separate and quantify the three basic vortex pinning contributions associated to anisotropic-strong, isotropic-strong and isotropic-weak pinning centers. The corresponding vortex pinning phase diagrams for these three contributions are built up. This methodol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
123
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 137 publications
(141 citation statements)
references
References 65 publications
(84 reference statements)
11
123
0
Order By: Relevance
“…Recently, researches of J c enhancement for REBCO films have been proceeded by introducing artificial pinning centers into the films. It has been reported that J c properties in magnetic fields were well improved for REBCO films with pinning centers such as RE 2 O 3 and BaZrO 3 nano compounds or Ce-Gd-O nanowalls by the MOD process using TFA salts [5][6][7][8][9]. On the other hand, we have been reported that BaSnO 3 nano rods acted stronger than BaZrO 3 as pinning centers in REBCO film grown by a pulsed laser deposition method [10].…”
Section: Introductionmentioning
confidence: 86%
“…Recently, researches of J c enhancement for REBCO films have been proceeded by introducing artificial pinning centers into the films. It has been reported that J c properties in magnetic fields were well improved for REBCO films with pinning centers such as RE 2 O 3 and BaZrO 3 nano compounds or Ce-Gd-O nanowalls by the MOD process using TFA salts [5][6][7][8][9]. On the other hand, we have been reported that BaSnO 3 nano rods acted stronger than BaZrO 3 as pinning centers in REBCO film grown by a pulsed laser deposition method [10].…”
Section: Introductionmentioning
confidence: 86%
“…1 Electric power applications such as motors and generators, require engineering critical current densities of 30 to 40 kA cm -² at 55 to 65 K in operating fields of 3 to 5 T. 2 Unfortunately, YBCO films typically exhibit a strong reduction of the critical current density (Jc) with increasing magnetic field strength caused by vortex motion. 3 The incorporation of nano-sized defects has proven to be an effective approach to achieve the immobilization of vortices, i.e. flux pinning.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the nucleation and growth mechanisms for this modified solutions should be further analyzed to ensure best performance. The modification of the solutions intends to reach more environmental friendly processes, enhanced thickness, planarized final HTS layers and generation of artificial pinning centers by growing nanocomposites [8] [9]. For that reasons, different additives in the precursor solutions have been used in the form of organic molecules (monomers or polymers) or inorganic salts [10] [11].…”
Section: Introductionmentioning
confidence: 99%